2009
DOI: 10.1071/ea08249
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of steer daily and residual feed intake in two tropical beef genotypes, and relationships among intake, body composition, growth and other post-weaning measures

Abstract: Abstract. Genetic parameters for Brahman (BRAH) and Tropical Composite (TCOMP) cattle were estimated for steer production traits recorded at weaning (WEAN), 80 days post-weaning (POSTW), feedlot entry (ENTRY) and after $120 days feedlot finishing (EXIT). The TCOMP was 50% Bos indicus, African Sanga or other tropically adapted Bos taurus, and 50% non-tropically adapted Bos taurus. Data involved 2216 steers, comprising 1007 BRAH by 53 sires and 1209 TCOMP by 50 sires. Individual daily feed intake (DFI) and resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
48
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 39 publications
8
48
1
Order By: Relevance
“…Genetic associations exist between growth traits and body composition attributes such as retail beef yield, fat depth and marbling (the review of Burrow et al, 2001 and references therein; Reverter et al, 2003a andWolcott et al, 2009) and feed efficiency (Robinson and Oddy, 2004;Barwick et al, 2009a). Genetic and phenotypic associations also exist between growth and reproductive attributes (Burrow et al, 1991;Burrow, 2001 and references therein).…”
Section: Are the Traits Under Genetic Control?mentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic associations exist between growth traits and body composition attributes such as retail beef yield, fat depth and marbling (the review of Burrow et al, 2001 and references therein; Reverter et al, 2003a andWolcott et al, 2009) and feed efficiency (Robinson and Oddy, 2004;Barwick et al, 2009a). Genetic and phenotypic associations also exist between growth and reproductive attributes (Burrow et al, 1991;Burrow, 2001 and references therein).…”
Section: Are the Traits Under Genetic Control?mentioning
confidence: 99%
“…Barwick et al (2009a) found that in steers grown under commercial backgrounding and grain-finishing environments, G 3 E interactions were indicated by the presence of significant genotype 3 cohort effects, with the mean cohort performance for a trait assumed to be the measure of environment level. Significant genotype 3 cohort effects existed for many measures at and before the steers entered the feedlot, indicating the differences evident in Brahmans and Tropical Composites could change under different environmental conditions.…”
Section: G 3 E Interactionsmentioning
confidence: 99%
“…In the feedlot, they were fed a standard finisher ration of 12.2 MJ ME/kg DM energy density, 16.25% crude protein (w/w) and 87% DM for an average of 119 days to a finished average liveweight of 568 kg. Other details of the management of steers are given by Barwick et al (2009).…”
Section: Management and Treatmentmentioning
confidence: 99%
“…Heifers born and managed together at 'Belmont' represented 34 BRAH and 26 TCOMP sires. Other details of sire and dam groups in the TCOMP genotype, and of the BRAH and TCOMP sires used are given by Barwick et al (2009). Briefly, the 50% tropically adapted component of the TCOMP is approximately one-half derived from the Bos indicus Brahman and one-half from African Sanga (Frisch et al 1997) (24% Africander) or other adapted Bos taurus (2% N'Dama, through the Senepol).…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation